Improving Economic and Social Outcomes through the Padat Karya Tunai Program: A Participatory Action Research Study on Rural Development in East Java - Triwahyudi, Yoki; Yulianis, M. Sifa Fauzi; Renggana, Yunus (STAI Miftahul ULa Nganjuk, 2024)
The Padat Karya Tunai (PKT) program, a government initiative providing temporary employment and infrastructure development, aims to reduce poverty and unemployment in rural Indonesia. This study utilizes Participatory Action Research (PAR) methodology to assess the program’s impact on economic advancement, community participation, and overall social development in East Java. Combining quantitative surveys with qualitative interviews and focus group discussions, this research evaluates changes in income, employment, and community involvement. The findings reveal a 25% increase in household income and a 70% improvement in employment status among participants. The program also contributed to the enhancement of local infrastructure and increased community cohesion. Despite these positive outcomes, challenges related to the temporary nature of employment and the program’s long-term sustainability were identified. The study emphasizes the need for vocational training and entrepreneurial support to provide lasting economic opportunities. The results suggest that while the PKT program is successful in addressing immediate needs, its long-term impact depends on continued capacity development and inclusive approaches. Recommendations include improving program management and broadening its reach to ensure more sustained benefits for rural communities.